Social values and propaganda: Theoretical perspectives of key concepts - Farcaş, Ana-Daniela (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales)

(untitled) (Département de communication sociale et publique, Université du Québec à Montréal, 2024)
From the negative connotation it receives in Marx’s theory to the idea that from birth we live in a network that is imbued with it, as Mannheim claims, ideology has always aroused the interest of researchers. The promotion of an ideology, and the change of one by another, is made possible by propaganda. However, for propaganda to succeed in promoting an ideology legitimizing a certain course of events, it must be based on a series of values deeply rooted in society. The propagandist discourse will appeal to the axiological universe to motivate and mask actions, facts, and ways of thinking. From a political point of view, all forms of societies use propaganda; in this regard, it is important to look at how varied the values used in propaganda discourse are and what they are masking.